Establishing an evidence hub for CGIAR's GENDER Platform - KREA University (KREA University, 2020)
The new CGIAR GENDER Platform will contribute to the One CGIAR mission of ending hunger through science-driven transformation of food, land and water systems in the context of climate change, by reimagining the CGIAR gender-research-for-development agenda. We envision a new era in which food systems transformation and gender equality reinforce one another, accelerating and amplifying benefits that are equitable, sustainable and lasting. This report outlines the broad scope for developing an evidence hub that will be integrated with the Platform resource centre and highlights best practices and examples in establishing a user-friendly knowledge hub.